A method for efficiently deconstructing lignocellulose raw materials by coupling carbon dioxide with organic solvents

By using the combination of CO2, metal chloride and organic solvents, the directional deconstruction and component selectivity of wood cellulose are used to solve the problem of strict treatment and poor effects in the existing pre -processing methods, and the fiber is achieved, and fiber is achieved. Successful and environmentally friendly processing process.

CN115928479BActive Publication Date: 2025-01-24ANHUI POLYTECHNIC UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211439165.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-17
Publication Date
2025-01-24
Estimated Expiration
2042-11-17

AI Technical Summary

Technical Problem

The existing pretreatment methods for lignocellulose raw materials have problems such as severe treatment conditions (high temperature, high pressure and long-term), high equipment requirements, high processing costs and poor treatment effects.

Method used

The carbon dioxide (CO2) is used as a compressed gas, and the metal chloride is used as a synergistic catalyst. Organic solvents are used as a medium that maintains stable response temperature and dissolved components.

Benefits of technology

It effectively avoids cellulose loss, improves lignin removal efficiency, has mild treatment conditions, is environmentally friendly and safe, and achieves directional separation and enrichment of lignocellulose components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115928479B_ABST
    Figure CN115928479B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for efficiently deconstructing lignocellulose raw materials by coupling carbon dioxide with an organic solvent, comprising: washing, drying and crushing agricultural and forestry processing waste to obtain materials; mixing the crushed materials with a reaction solvent, adding metal chloride, ultrasonically treating the mixed materials to exhaust, placing them in a reactor, replacing the air in the reactor with CO2, heating them under normal pressure or pressure, filtering the materials, washing the solid residue with water until it is neutral, and vacuum freeze-drying them to obtain crude cellulose; wherein the reaction solvent is a mixture of an organic solvent and water in a volume ratio of 75:25 to 100:0; and the organic solvent is an organic solvent with a boiling point of 150 to 300°C. The present invention has mild and safe processing conditions, and can realize directional deconstruction of lignocellulose by low pressure and heating treatment, while non-destructively recovering cellulose, selectively separating a large amount of lignin and hemicellulose, and promoting the enrichment of cellulose in the solid phase.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of wood fiber biomass chemical industry, and relates to a method for efficiently deconstructing wood cellulose raw materials by coupling carbon dioxide with an organic solvent, and specifically relates to a method for directional separation of components by low-pressure pretreatment of wood cellulose by coupling carbon dioxide with an organic solvent. Background Art

[0002] With the acceleration of the world's industrialization process, the contradiction between the non-renewable nature of traditional petrochemical resources and the growing production and living needs of mankind has gradually intensified, especially the greenhouse effect caused by the excessive use of fossil fuels has become more and more serious. At present, the resource utilization of CO2 has become a research hotspot at home and abroad. Studies have shown that CO2 can be used to synthesize a variety of fine chemicals and fuels, such as methane, methanol, carbonates, starch, etc., but they are currently at the laboratory level and still have problems such as slow CO2 conversion rate, low carbon fixation efficiency, and poor product selectivity. Although supercritical CO2 can replace organic solvents as an extractant, it is difficult to extract substances with strong polarity and large molecular weight (such as polysaccharides), and its application has limitations.

[0003] On the other hand, lignocellulosic raw materials (such as agricultural and forestry processing waste) have become the main raw material resource in the world today to replace traditional petrochemical resources and achieve sustainable production of energy and bio-based chemicals due to their annual production of hundreds of billions of tons. However, lignocellulose has a dense structure and complex composition, and direct use will have defects such as high energy consumption and low selectivity for target products. Therefore, lignocellulosic raw materials need to be pretreated to destroy their physical barriers, selectively separate hemicellulose and lignin, and enrich cellulose for the preparation of high-value products such as biodiesel, ethanol, and hydrogen.

[0004] The study found that CO2 can be ionized to produce H by hydration to form H2CO3 (weak acid electrolyte). + , acidification treatment environment, especially when pressurized or heated, the H in the CO2 / water system + The concentration increases, while the CO2 can be recovered by reducing pressure or cooling. Based on the characteristics of CO2, domestic and foreign scholars have tried to use CO2 to pretreat lignocellulosic raw materials for component separation. Park et al. reviewed the research progress on CO2 pretreatment methods in recent years and found that although the CO2 coupled hydrothermal pretreatment method is simple to operate and low in cost, the separation effect of the "three elements" is poor. The main reason is that the catalytic mechanism of CO2 is similar to that of traditional B acid, both of which are H +The effect, combined with high temperature, high pressure and long time, is easy to cause the loss of cellulose, and the aqueous solution is not conducive to the dissolution of lignin. Ge et al. hydrothermally pretreated peanut shells (200℃, 1h) and simultaneously pressurized with CO2 (6MPaCO2), which increased the lignin content in the treated matrix to 47%. Similarly, Xu Junming et al. also found that after the poplar wood was hydrothermally pretreated (180℃, 2MPaCO2, 10min), although a large amount of hemicellulose was removed, the lignin removal rate was only 15%, and 10% of cellulose was lost. Summary of the invention

[0005] The purpose of the present invention is to provide a method for efficiently deconstructing lignocellulose raw materials by coupling carbon dioxide with organic solvents, in order to address the problems of severe treatment conditions (high temperature, high pressure and long time), high equipment requirements, high treatment costs and poor treatment effects in existing lignocellulose raw material pretreatment methods. The method uses CO2 as a pressurized gas, a metal chloride as a synergistic catalyst, and an organic solvent as a medium for maintaining a stable reaction temperature and dissolving components (lignin and hemicellulose). The treatment conditions are adjusted to achieve directional deconstruction of lignocellulose and selective separation of components, which can effectively avoid cellulose loss and improve the removal efficiency of lignin.

[0006] The objective of the present invention is achieved through the following technical solutions:

[0007] A method for efficiently deconstructing lignocellulose raw materials by coupling carbon dioxide with an organic solvent, comprising: washing, drying and crushing agricultural and forestry processing waste to obtain materials; mixing the crushed materials with a reaction solvent, adding a metal chloride, ultrasonically treating the mixed materials to exhaust the gas, and then placing the mixed materials in a reactor, replacing the air in the reactor with CO2, heating the reactor under normal pressure or pressure to separate lignocellulose components, filtering the materials, washing the solid residue with water to neutrality, and vacuum freeze-drying to obtain crude cellulose.

[0008] The agricultural and forestry processing waste is one or more of rice straw, wheat straw, cotton straw, eucalyptus, birch, poplar and switchgrass.

[0009] The drying method includes: drying the material at 105°C with air blast until the moisture content of the material is 0-10%, so as to avoid excessive moisture in the material during heating, which may reduce the specific gravity of the organic solvent when it enters the material, thereby affecting the dissolution of the wood cellulose component.

[0010] The agricultural and forestry processing waste is crushed to obtain materials with a size of 20 to 40 meshes. Controlling the size of the materials to 20 to 40 meshes can prevent the cellulose structure from being damaged and causing its loss.

[0011] Specifically, the crushing is as follows: the agricultural and forestry processing waste is first cut into a length of 2 to 8 cm by a guillotine, then crushed by a mechanical crusher, and sieved to obtain a material of 20 to 40 meshes.

[0012] Considering that the viscosity of the organic solvent will affect the uniform dispersion of the material in the system, deionized water can be added, but it is necessary to avoid reducing the dissolution of lignin and the boiling point of the system when the water specific gravity in the reaction system is too large. The reaction solvent is a mixture of an organic solvent and water in a volume ratio (v / v) of 75:25 to 100:0, preferably a mixture of an organic solvent and water in a volume ratio of 80:20 to 100:0, and more preferably a mixture of an organic solvent and water in a volume ratio of 80:20 to 90:10.

[0013] The organic solvent is an organic solvent with a boiling point of 150-300°C.

[0014] Specifically, the organic solvent is one of tetrahydrofurfuryl alcohol, 1,2-propylene glycol, glycerol, diethylene glycol, and ethylene glycol, preferably ethylene glycol.

[0015] The metal chloride is one of FeCl3 and AlCl3.

[0016] The concentration of the metal chloride in the reaction solvent is 0.05-0.15 mol / L, preferably 0.08-0.1 mol / L.

[0017] The usage ratio of the agricultural and forestry processing waste to the metal chloride is 1:0.001 to 1:0.003 g / mol, preferably 1:0.0016 to 1:0.002 g / mol.

[0018] The reactor is a high temperature and high pressure resistant stainless steel reactor, and the reactor is heated by electric heating.

[0019] The power of the ultrasonic treatment is 150W and the time is 5 minutes.

[0020] As a preferred technical solution for the method of efficiently deconstructing lignocellulose raw materials by coupling carbon dioxide with organic solvents described in the present invention, it includes: before heating treatment, CO2 is introduced to exhaust the air in the reaction kettle cavity and fill it with CO2 to avoid air interference, prevent oxygen therein from oxidizing the active groups of lignocellulose, and increase the solubility of CO2 in the reaction solvent.

[0021] The normal pressure or pressurized pressure is: the pressure of CO2 is 0.1-2MPa, preferably 0.1-1MPa.

[0022] The heating treatment is as follows: the temperature is raised from room temperature to 110-190° C. at a heating rate of 4-5° C. / min while stirring, and the temperature is kept for 0-45 minutes, and then the temperature is quickly lowered to room temperature by cooling in an ice water bath.

[0023] Preferably, the heating treatment is: heating from room temperature to 150-190° C. at a heating rate of 4-5° C. / min while stirring, and keeping the temperature for 5-30 minutes, and then cooling rapidly to room temperature in an ice water bath.

[0024] More preferably, the heating treatment is: heating from room temperature to 150-170° C. at a heating rate of 4-5° C. / min while stirring, and keeping the temperature for 5-30 minutes, and then cooling rapidly to room temperature in an ice water bath.

[0025] More specifically, during the heat treatment, the insulation time may be 0 to 45 min, 0 to 30 min, 0 to 15 min, 0 to 10 min, or 0 to 5 min.

[0026] The stirring speed is 600-1000 rpm. Specifically, magnetic stirring can be used.

[0027] As a preferred technical solution of the method of efficiently deconstructing lignocellulose raw materials by coupling carbon dioxide with organic solvents described in the present invention, it includes: reducing pressure and recovering CO2 during cooling in an ice-water bath.

[0028] Specifically, a method for efficiently deconstructing lignocellulose raw materials by coupling carbon dioxide with an organic solvent comprises the following steps:

[0029] Step (1): washing, drying, crushing and sieving agricultural and forestry processing waste to obtain materials with a mesh size of 20 to 40;

[0030] Step (2): the material obtained in step (1) is mixed with a reaction solvent, a metal chloride is added, the mixed material is subjected to ultrasonic treatment to exhaust the gas, and then placed in a reactor, the air in the reactor is replaced with CO2, CO2 is added for pressurization, and the temperature is raised from room temperature to 110-190°C at a rate of 4-5°C / min while stirring, and the temperature is kept stirred for 0-45 minutes, and the material is cooled to room temperature in an ice-water bath, and the material is filtered, the solid residue is washed with water until it is neutral, and vacuum freeze-dried to obtain crude cellulose.

[0031] The method of the present invention realizes the enrichment of cellulose in agricultural and forestry processing wastes, and the obtained crude cellulose can be used to produce high-value products such as biodiesel, ethanol, hydrogen, etc. after hydrolysis.

[0032] The room temperature is 25-30℃.

[0033] The crude cellulose of the present invention has a cellulose content of 68-75%.

[0034] Beneficial effects of the present invention:

[0035] 1. The lignocellulose raw material of the present invention is a renewable and sustainable resource, which is easily available, cheap and widely available;

[0036] 2. CO2 is not only a pressurized gas, but its aqueous solution is acidic, and the H + It can effectively catalyze the depolymerization of lignocellulose, and CO2 can be recovered by decompression and recycled for pretreatment of lignocellulose raw materials; in addition, high-boiling point organic solvents can increase the solubility of CO2 in the system, maintain the temperature of the system stable, and enhance the depolymerization of lignocellulose.

[0037] 3. The method of the present invention has mild treatment conditions, is relatively environmentally friendly, and has high safety. Low pressure and heating treatment can achieve directional separation of lignocellulose components, and organic solvents selectively dissolve a large amount of lignin and hemicellulose. At the same time, a small amount of fermentation inhibitors such as formic acid, furfural, and acetic acid produced by acid hydrolysis of cellulose polysaccharides are dissolved in the liquid phase. While recovering cellulose without loss, a large amount of lignin and hemicellulose are selectively separated, and cellulose is enriched in the solid phase. The cellulose recovery rate of agricultural and forestry processing waste is 92-100%, the hemicellulose removal rate is 70-92%, and the lignin removal rate is 84-92%. Under the preferred technical scheme of the present invention, the cellulose content in the obtained crude cellulose is 68-75%, the hemicellulose content is 2-8%, and the lignin content is 4-5%. The crystallinity of crude cellulose is 40-60%.

[0038] 4. The present invention provides technical support for high-value utilization of CO2. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 This is the XRD spectrum of the original rice straw and crude cellulose in Example 1. DETAILED DESCRIPTION

[0040] In order to make those skilled in the art better understand the technical solution of the present invention, the present invention is further described in detail below in conjunction with specific embodiments. Those skilled in the art can appropriately improve the process parameters under the guidance of the present invention. It is particularly important to point out that all similar replacements and modifications are obvious to those skilled in the art, and they are all considered to be included in the present invention.

[0041] Example 1

[0042] The rice straw (containing 29% cellulose, 18% hemicellulose and 18% lignin) was washed and desanded, dried at 105°C for 8 hours to a moisture content of 0%, cut into pieces of 2 to 8 cm in length by a guillotine, and then crushed by a mechanical crusher and sieved to obtain pieces of 20 to 40 mesh. 3 g of crushed rice straw, 60 mL of ethylene glycol-water solution (ethylene glycol: water = 90:10 v / v) and ferric chloride hexahydrate were placed in a quartz liner, and the concentration of ferric chloride hexahydrate in the ethylene glycol-water solution was 0.1 mol / L. The material in the quartz liner was ultrasonically treated to remove the gas in the solvent (150 W, 5 min), and then the quartz liner was placed in a stainless steel reactor body (100 mL; NSG100-P5-T3-SS1-SV-R, Anhui Ke Mi Instrument Co., Ltd.), the reactor cover was closed, and after sealing, CO2 was introduced into the reactor body, and the blowing was repeated for 2 to 5 min. The air in the reactor cavity was exhausted by CO2, and the reactor was pressurized (1 MPa). CO2), magnetic stirring (600rpm) was used to ensure uniform mixing throughout the process, and the temperature was monitored by a thermocouple above the kettle cover, rising from 30°C to 150°C within 30 minutes and keeping warm for 5 minutes; the kettle was taken out, treated in an ice water bath for 5 minutes, cooled to 30°C, the quartz lining was taken out, and a sand core funnel (G1-100mL) was used for vacuum filtration to obtain a solid residue. The solid residue was washed 3 times with deionized water (100mL deionized water each time) until the filtrate was neutral to obtain crude cellulose.

[0043] As shown in Table 1, the cellulose content in the crude cellulose reached 68%, and the hemicellulose and lignin contents were 7% and 5%, respectively, that is, 100% of the cellulose in the original rice straw was retained, while 83% of the hemicellulose and 88% of the lignin were removed.

[0044] like Figure 1 As shown in Figure 2, after the rice straw was treated with CO2-ethylene glycol-ferric chloride-water, the cellulose crystal form did not change, but its crystallinity increased from 30% to 55%, and the specific surface area increased from 2.8m 2 / g increased to 12.6m 2 Compared with the rice straw not treated in this example, the adsorption efficiency of crude cellulose on cellulase increased by 2.8 times, indicating that the pretreatment effectively improved the enzymatic hydrolysis of rice straw.

[0045] Example 2

[0046] 3 g of crushed rice straw (same as in Example 1), 60 mL of ethylene glycol-water solution (ethylene glycol: water = 90:10 v / v) and ferric chloride hexahydrate were placed in a quartz liner, the concentration of ferric chloride hexahydrate in the ethylene glycol-water solution was 0.1 mol / L, the material in the quartz liner was ultrasonically treated and exhausted (150 W, 5 min), and then the quartz liner was placed in a stainless steel reactor body (100 mL; NSG100-P5-T3-SS1-SV-R, Anhui Ke Mi Instrument Co., Ltd.), the reactor cover was closed, and after sealing, CO2 was used to exhaust the air in the reactor cavity (repeatedly blown for 2 to 5 min), and pressurized (1 MPaCO2), and magnetic stirring (600 rpm) was used throughout the process to ensure uniform mixing, and the temperature was monitored by a thermocouple above the reactor cover, and the temperature was raised from 30°C to 150°C within 30 min and kept warm for 10 min. The kettle was taken out, treated in an ice-water bath for 5 minutes, cooled to 30°C, the quartz lining was taken out, and a sand core funnel (G1-100mL) was used for vacuum filtration to obtain a solid residue. The solid residue was washed with deionized water for 3 times (100mL deionized water each time) until the filtrate was neutral to obtain crude cellulose.

[0047] Example 3

[0048] 3 g of crushed rice straw (same as in Example 1), 60 mL of ethylene glycol-water solution (ethylene glycol: water = 90:10 v / v) and ferric chloride hexahydrate were placed in a quartz liner, the concentration of ferric chloride hexahydrate in the ethylene glycol-water solution was 0.1 mol / L, the material in the quartz liner was ultrasonically treated and exhausted (150 W, 5 min), and then the quartz liner was placed in a stainless steel reactor body (100 mL; NSG100-P5-T3-SS1-SV-R, Anhui Ke Mi Instrument Co., Ltd.), the reactor cover was closed, and after sealing, CO2 was used to exhaust the air in the reactor cavity (repeatedly blown for 2 to 5 min), and pressurized (1 MPaCO2), and magnetic stirring (600 rpm) was used throughout the process to ensure uniform mixing, and the temperature was monitored by a thermocouple above the reactor cover, and the temperature was raised from 30°C to 150°C within 30 min and kept warm for 15 min. The kettle was taken out, treated in an ice-water bath for 5 minutes, cooled to 30°C, the quartz lining was taken out, and a sand core funnel (G1-100mL) was used for vacuum filtration to obtain a solid residue. The solid residue was washed with deionized water for 3 times (100mL deionized water each time) until the filtrate was neutral to obtain crude cellulose.

[0049] Example 4

[0050] 3 g of crushed rice straw (same as in Example 1), 60 mL of ethylene glycol-water solution (ethylene glycol: water = 90:10 v / v) and ferric chloride hexahydrate were placed in a quartz liner, the concentration of ferric chloride hexahydrate in the ethylene glycol-water solution was 0.1 mol / L, the material in the quartz liner was ultrasonically treated and exhausted (150 W, 5 min), and then the quartz liner was placed in a stainless steel reactor body (100 mL; NSG100-P5-T3-SS1-SV-R, Anhui Ke Mi Instrument Co., Ltd.), the reactor cover was closed, and after sealing, CO2 was used to exhaust the air in the reactor cavity (repeatedly blown for 2 to 5 min), and pressurized (1 MPaCO2), and magnetic stirring (600 rpm) was used throughout the process to ensure uniform mixing, and the temperature was monitored by a thermocouple above the reactor cover, and the temperature was raised from 30°C to 150°C within 30 min and kept warm for 30 min. The kettle was taken out, treated in an ice-water bath for 5 minutes, cooled to 30°C, the quartz lining was taken out, and a sand core funnel (G1-100mL) was used for vacuum filtration to obtain a solid residue. The solid residue was washed with deionized water for 3 times (100mL deionized water each time) until the filtrate was neutral to obtain crude cellulose.

[0051] Example 5

[0052] 3 g of crushed rice straw (same as in Example 1), 60 mL of ethylene glycol-water solution (ethylene glycol: water = 90:10 v / v) and ferric chloride hexahydrate were placed in a quartz liner, the concentration of ferric chloride hexahydrate in the ethylene glycol-water solution was 0.1 mol / L, the material in the quartz liner was ultrasonically treated and exhausted (150 W, 5 min), and then the quartz liner was placed in a stainless steel reactor body (100 mL; NSG100-P5-T3-SS1-SV-R, Anhui Ke Mi Instrument Co., Ltd.), the reactor cover was closed, and after sealing, CO2 was used to exhaust the air in the reactor cavity (repeatedly blown for 2 to 5 min), and pressurized (1 MPaCO2), and magnetic stirring (600 rpm) was used throughout the process to ensure uniform mixing, and the temperature was monitored by a thermocouple above the reactor cover, rising from 30°C to 150°C within 30 min and keeping warm for 45 min. The kettle was taken out, treated in an ice-water bath for 5 minutes, cooled to 30°C, the quartz lining was taken out, and a sand core funnel (G1-100mL) was used for vacuum filtration to obtain a solid residue. The solid residue was washed with deionized water for 3 times (100mL deionized water each time) until the filtrate was neutral to obtain crude cellulose.

[0053] Example 6

[0054] 3 g of crushed rice straw (same as in Example 1), 60 mL of ethylene glycol-water solution (ethylene glycol: water = 90:10 v / v) and ferric chloride hexahydrate were placed in a quartz liner, the concentration of ferric chloride hexahydrate in the ethylene glycol-water solution was 0.1 mol / L, the material in the quartz liner was ultrasonically treated and exhausted (150 W, 5 min), and then the quartz liner was placed in a stainless steel reactor body (100 mL; NSG100-P5-T3-SS1-SV-R, Anhui Ke Mi Instrument Co., Ltd.), the reactor cover was closed, and after sealing, CO2 was used to exhaust the air in the reactor cavity (repeatedly blown for 2 to 5 min), and pressurized (1 MPaCO2), and magnetic stirring (600 rpm) was used throughout the process to ensure uniform mixing, and the temperature was monitored by a thermocouple above the reactor cover, rising from 30°C to 110°C within 20 min and keeping warm for 5 min. The kettle was taken out, treated in an ice-water bath for 5 minutes, cooled to 30°C, the quartz lining was taken out, and a sand core funnel (G1-100mL) was used for vacuum filtration to obtain a solid residue. The solid residue was washed with deionized water for 3 times (100mL deionized water each time) until the filtrate was neutral to obtain crude cellulose.

[0055] Example 7

[0056] 3 g of crushed rice straw (same as in Example 1), 60 mL of ethylene glycol-water solution (ethylene glycol: water = 90:10 v / v) and ferric chloride hexahydrate were placed in a quartz liner, the concentration of ferric chloride hexahydrate in the ethylene glycol-water solution was 0.1 mol / L, the material in the quartz liner was ultrasonically treated and exhausted (150 W, 5 min), and then the quartz liner was placed in a stainless steel reactor body (100 mL; NSG100-P5-T3-SS1-SV-R, Anhui Ke Mi Instrument Co., Ltd.), the reactor cover was closed, and after sealing, CO2 was used to exhaust the air in the reactor cavity (repeatedly blown for 2 to 5 min), and pressurized (1 MPaCO2), and magnetic stirring (600 rpm) was used throughout the process to ensure uniform mixing, and the temperature was monitored by a thermocouple above the reactor cover, rising from 30°C to 130°C within 20 min and keeping warm for 5 min. The kettle was taken out, treated in an ice-water bath for 5 minutes, cooled to 30°C, the quartz lining was taken out, and a sand core funnel (G1-100mL) was used for vacuum filtration to obtain a solid residue. The solid residue was washed with deionized water for 3 times (100mL deionized water each time) until the filtrate was neutral to obtain crude cellulose.

[0057] Example 8

[0058] 3 g of crushed rice straw (same as in Example 1), 60 mL of ethylene glycol-water solution (ethylene glycol: water = 90:10 v / v) and ferric chloride hexahydrate were placed in a quartz liner, the concentration of ferric chloride hexahydrate in the ethylene glycol-water solution was 0.1 mol / L, the material in the quartz liner was ultrasonically treated and exhausted (150 W, 5 min), and then the quartz liner was placed in a stainless steel reactor body (100 mL; NSG100-P5-T3-SS1-SV-R, Anhui Ke Mi Instrument Co., Ltd.), the reactor cover was closed, and after sealing, CO2 was used to exhaust the air in the reactor cavity (repeatedly blown for 2 to 5 min), and pressurized (1 MPaCO2), and magnetic stirring (600 rpm) was used throughout the process to ensure uniform mixing, and the temperature was monitored by a thermocouple above the reactor cover, rising from 30°C to 170°C within 30 min and keeping warm for 5 min. The kettle was taken out, treated in an ice-water bath for 5 minutes, cooled to 30°C, the quartz lining was taken out, and a sand core funnel (G1-100mL) was used for vacuum filtration to obtain a solid residue. The solid residue was washed with deionized water for 3 times (100mL deionized water each time) until the filtrate was neutral to obtain crude cellulose.

[0059] Example 9

[0060] 3 g of crushed rice straw (same as in Example 1), 60 mL of ethylene glycol-water solution (ethylene glycol: water = 90:10 v / v) and ferric chloride hexahydrate were placed in a quartz liner, the concentration of ferric chloride hexahydrate in the ethylene glycol-water solution was 0.1 mol / L, the material in the quartz liner was ultrasonically treated and exhausted (150 W, 5 min), and then the quartz liner was placed in a stainless steel reactor body (100 mL; NSG100-P5-T3-SS1-SV-R, Anhui Ke Mi Instrument Co., Ltd.), the reactor cover was closed, and after sealing, CO2 was used to exhaust the air in the reactor cavity (repeatedly blown for 2 to 5 min), and pressurized (1 MPaCO2), and magnetic stirring (600 rpm) was used throughout the process to ensure uniform mixing, and the temperature was monitored by a thermocouple above the reactor cover, rising from 30 ° C to 190 ° C within 35 min, and kept warm for 5 min. The kettle was taken out, treated in an ice-water bath for 5 minutes, cooled to 30°C, the quartz lining was taken out, and a sand core funnel (G1-100mL) was used for vacuum filtration to obtain a solid residue. The solid residue was washed with deionized water for 3 times (100mL deionized water each time) until the filtrate was neutral to obtain crude cellulose.

[0061] Example 10

[0062] 3 g of crushed rice straw (same as in Example 1), 60 mL of ethylene glycol-water solution (ethylene glycol: water = 75:25 v / v) and ferric chloride hexahydrate were placed in a quartz liner, the concentration of ferric chloride hexahydrate in the ethylene glycol-water solution was 0.1 mol / L, the material in the quartz liner was ultrasonically treated and exhausted (150 W, 5 min), and then the quartz liner was placed in a stainless steel reactor body (100 mL; NSG100-P5-T3-SS1-SV-R, Anhui Ke Mi Instrument Co., Ltd.), the reactor cover was closed, and after sealing, CO2 was used to exhaust the air in the reactor cavity (repeatedly blown for 2 to 5 min), and pressurized (1 MPaCO2), and magnetic stirring (600 rpm) was used throughout the process to ensure uniform mixing, and the temperature was monitored by a thermocouple above the reactor cover, rising from 30°C to 170°C within 30 min and keeping warm for 5 min. The kettle was taken out, treated in an ice-water bath for 5 minutes, cooled to 30°C, the quartz lining was taken out, and a sand core funnel (G1-100mL) was used for vacuum filtration to obtain a solid residue. The solid residue was washed with deionized water for 3 times (100mL deionized water each time) until the filtrate was neutral to obtain crude cellulose.

[0063] Embodiment 11

[0064] 3 g of crushed rice straw (same as in Example 1), 60 mL of ethylene glycol-water solution (ethylene glycol: water = 80:20 v / v) and ferric chloride hexahydrate were placed in a quartz liner, the concentration of ferric chloride hexahydrate in the ethylene glycol-water solution was 0.1 mol / L, the material in the quartz liner was ultrasonically treated and exhausted (150 W, 5 min), and then the quartz liner was placed in a stainless steel reactor body (100 mL; NSG100-P5-T3-SS1-SV-R, Anhui Ke Mi Instrument Co., Ltd.), the reactor cover was closed, and after sealing, CO2 was used to exhaust the air in the reactor cavity (repeatedly blown for 2 to 5 min), and pressurized (1 MPaCO2), and magnetic stirring (600 rpm) was used throughout the process to ensure uniform mixing, and the temperature was monitored by a thermocouple above the reactor cover, rising from 30°C to 170°C within 30 min and keeping warm for 5 min. The kettle was taken out, treated in an ice-water bath for 5 minutes, cooled to 30°C, the quartz lining was taken out, and a sand core funnel (G1-100mL) was used for vacuum filtration to obtain a solid residue. The solid residue was washed with deionized water for 3 times (100mL deionized water each time) until the filtrate was neutral to obtain crude cellulose.

[0065] Example 12

[0066] 3g of crushed rice straw (same as in Example 1), 60mL of ethylene glycol and ferric chloride hexahydrate were loaded into the quartz liner, the concentration of ferric chloride hexahydrate in ethylene glycol was 0.1mol / L, the material in the quartz liner was ultrasonically treated and exhausted (150W, 5min), and then the quartz liner was placed in a stainless steel reactor (100mL; NSG100-P5-T3-SS1-SV-R, Anhui Kemi Instrument Co., Ltd.), the reactor cover was covered, and after sealing, CO2 was used to exhaust the air in the reactor cavity (repeatedly blown for 2-5min), pressurized (1MPaCO2), and magnetic stirring (600rpm) was used throughout the process to ensure uniform mixing. The temperature was monitored by a thermocouple above the reactor cover, and it rose from 30°C to 170°C within 30min, and kept warm for 5min. The reactor was taken out, treated in an ice water bath for 5min, cooled to 30°C, the quartz liner was taken out, and a sand core funnel (G1-100mL) was used to vacuum filter to obtain a solid residue. The solid residue was washed with deionized water three times (100 mL of deionized water each time) until the filtrate was neutral to obtain crude cellulose.

[0067] Example 13

[0068] 3 g of crushed rice straw (same as in Example 1), 60 mL of ethylene glycol-water solution (ethylene glycol: water = 90:10 v / v) and ferric chloride hexahydrate were placed in a quartz liner, the concentration of ferric chloride hexahydrate in the ethylene glycol-water solution was 0.05 mol / L, the material in the quartz liner was ultrasonically treated and exhausted (150 W, 5 min), and then the quartz liner was placed in a stainless steel reactor body (100 mL; NSG100-P5-T3-SS1-SV-R, Anhui Ke Mi Instrument Co., Ltd.), the reactor cover was closed, and after sealing, CO2 was used to exhaust the air in the reactor cavity (repeatedly blown for 2 to 5 min), and pressurized (1 MPaCO2), and magnetic stirring (600 rpm) was used throughout the process to ensure uniform mixing, and the temperature was monitored by a thermocouple above the reactor cover, rising from 30°C to 170°C within 30 min and keeping warm for 5 min. The kettle was taken out, treated in an ice-water bath for 5 minutes, cooled to 30°C, the quartz lining was taken out, and a sand core funnel (G1-100mL) was used for vacuum filtration to obtain a solid residue. The solid residue was washed with deionized water for 3 times (100mL deionized water each time) until the filtrate was neutral to obtain crude cellulose.

[0069] Embodiment 14

[0070] 3 g of crushed rice straw (same as in Example 1), 60 mL of ethylene glycol-water solution (ethylene glycol: water = 90:10 v / v) and ferric chloride hexahydrate were placed in a quartz liner, the concentration of ferric chloride hexahydrate in the ethylene glycol-water solution was 0.08 mol / L, the material in the quartz liner was ultrasonically treated and exhausted (150 W, 5 min), and then the quartz liner was placed in a stainless steel reactor body (100 mL; NSG100-P5-T3-SS1-SV-R, Anhui Ke Mi Instrument Co., Ltd.), the reactor cover was closed, and after sealing, CO2 was used to exhaust the air in the reactor cavity (repeatedly blown for 2 to 5 min), and pressurized (1 MPaCO2), and magnetic stirring (600 rpm) was used throughout the process to ensure uniform mixing, and the temperature was monitored by a thermocouple above the reactor cover, rising from 30°C to 170°C within 30 min and keeping warm for 5 min. The kettle was taken out, treated in an ice-water bath for 5 minutes, cooled to 30°C, the quartz lining was taken out, and a sand core funnel (G1-100mL) was used for vacuum filtration to obtain a solid residue. The solid residue was washed with deionized water for 3 times (100mL deionized water each time) until the filtrate was neutral to obtain crude cellulose.

[0071] Embodiment 15

[0072] 3 g of crushed rice straw (same as in Example 1), 60 mL of ethylene glycol-water solution (ethylene glycol: water = 90:10 v / v) and ferric chloride hexahydrate were placed in a quartz liner, the concentration of ferric chloride hexahydrate in the ethylene glycol-water solution was 0.15 mol / L, the material in the quartz liner was ultrasonically treated and exhausted (150 W, 5 min), and then the quartz liner was placed in a stainless steel reactor body (100 mL; NSG100-P5-T3-SS1-SV-R, Anhui Ke Mi Instrument Co., Ltd.), the reactor cover was closed, and after sealing, CO2 was used to exhaust the air in the reactor cavity (repeatedly blown for 2 to 5 min), and pressurized (1 MPaCO2), and magnetic stirring (600 rpm) was used throughout the process to ensure uniform mixing, and the temperature was monitored by a thermocouple above the reactor cover, rising from 30°C to 170°C within 30 min and keeping warm for 5 min. The kettle was taken out, treated in an ice-water bath for 5 minutes, cooled to 30°C, the quartz lining was taken out, and a sand core funnel (G1-100mL) was used for vacuum filtration to obtain a solid residue. The solid residue was washed with deionized water for 3 times (100mL deionized water each time) until the filtrate was neutral to obtain crude cellulose.

[0073] Example 16

[0074] 3 g of crushed rice straw (same as in Example 1), 60 mL of ethylene glycol-water solution (ethylene glycol: water = 90:10 v / v) and ferric chloride hexahydrate were placed in a quartz liner, the concentration of ferric chloride hexahydrate in the ethylene glycol-water solution was 0.1 mol / L, the material in the quartz liner was ultrasonically treated for exhaust (150 W, 5 min), and then the quartz liner was placed in a stainless steel reactor (100 mL; NSG100-P5-T3-SS1-SV-R, Anhui Kemi Instrument Co., Ltd. Co., Ltd.), cover the kettle, seal it, use CO2 to exhaust the air in the reaction kettle cavity (repeatedly blow for 2 to 5 minutes), pressurize (1MPaCO2), and use magnetic stirring (600rpm) to ensure uniform mixing throughout the process. Monitor the temperature through the thermocouple above the kettle cover. When it rises from 30°C to 150°C within 30 minutes, take out the kettle immediately, treat it in an ice water bath for 5 minutes, cool it to 30°C, take out the quartz lining, and use a sand core funnel (G1-100mL) to vacuum filter to obtain solid residue. The solid residue is washed 3 times with deionized water (100mL deionized water each time) until the filtrate is neutral to obtain crude cellulose.

[0075] Embodiment 17

[0076] 3 g of crushed rice straw (same as in Example 1), 60 mL of ethylene glycol-water solution (ethylene glycol: water = 90:10 v / v) and aluminum chloride hexahydrate were placed in a quartz liner, the concentration of aluminum chloride hexahydrate in the ethylene glycol-water solution was 0.1 mol / L, the material in the quartz liner was ultrasonically treated and exhausted (150 W, 5 min), and then the quartz liner was placed in a stainless steel reactor body (100 mL; NSG100-P5-T3-SS1-SV-R, Anhui Ke Mi Instrument Co., Ltd.), the reactor cover was closed and sealed, and the air in the reactor cavity was exhausted by CO2 (repeatedly blown for 2 to 5 min), and pressurized (1 MPa CO2), and magnetic stirring (600 rpm) was used throughout the process to ensure uniform mixing, and the temperature was monitored by a thermocouple above the reactor cover, and the temperature was raised from 30°C to 150°C within 30 min and kept warm for 5 min. The kettle was taken out, treated in an ice-water bath for 5 minutes, cooled to 30°C, the quartz lining was taken out, and a sand core funnel (G1-100mL) was used for vacuum filtration to obtain a solid residue. The solid residue was washed with deionized water for 3 times (100mL deionized water each time) until the filtrate was neutral to obtain crude cellulose.

[0077] Embodiment 18

[0078] 3 g of crushed rice straw (same as in Example 1), 60 mL of glycerol-water solution (glycerol: water = 90:10 v / v) and aluminum chloride hexahydrate were placed in a quartz liner, the concentration of aluminum chloride hexahydrate in the glycerol-water solution was 0.1 mol / L, the material in the quartz liner was ultrasonically treated and exhausted (150 W, 5 min), and then the quartz liner was placed in a stainless steel reactor body (100 mL; NSG100-P5-T3-SS1-SV-R, Anhui Ke Mi Instrument Co., Ltd.), the reactor cover was closed and sealed, and the air in the reactor cavity was exhausted by CO2 (repeatedly blown for 2 to 5 min), and pressurized (1 MPa CO2), and magnetic stirring (600 rpm) was used throughout the process to ensure uniform mixing, and the temperature was monitored by a thermocouple above the reactor cover, rising from 30°C to 170°C within 30 min and keeping warm for 5 min. The kettle was taken out, treated in an ice-water bath for 5 minutes, cooled to 30°C, the quartz lining was taken out, and a sand core funnel (G1-100mL) was used for vacuum filtration to obtain a solid residue. The solid residue was washed with deionized water for 3 times (100mL deionized water each time) until the filtrate was neutral to obtain crude cellulose.

[0079] Comparative Example 1

[0080] 3g of crushed rice straw (same as in Example 1), 60mL of ethylene glycol-water solution (ethylene glycol: water = 90:10 v / v) and ferric chloride hexahydrate were placed in a quartz liner, the concentration of ferric chloride hexahydrate in the ethylene glycol-water solution was 0.1 mol / L, placed in a stainless steel reactor (100mL; NSG100-P5-T3-SS1-SV-R, Anhui Kemi Instrument Co., Ltd.), covered with a reactor cover, sealed, without pressurization, and magnetic stirring (600rpm) was used throughout to ensure uniform mixing. The temperature was monitored by a thermocouple above the reactor cover, and increased from 30°C to 150°C within 30min, and kept warm for 5min. The reactor was taken out, treated in an ice water bath for 5min, cooled to 30°C, the quartz liner was taken out, and a sand core funnel (G1-100mL) was used for vacuum filtration to obtain a solid residue. The solid residue was washed 3 times with deionized water (100mL deionized water each time) until the filtrate was neutral to obtain crude cellulose.

[0081] Comparative Example 2

[0082] 3g of crushed rice straw (same as in Example 1) and 60mL of ethylene glycol-water solution (ethylene glycol: water = 90:10 v / v) were placed in the quartz liner, and the material in the quartz liner was ultrasonically treated and exhausted (150W, 5min), and then the quartz liner was placed in a stainless steel reactor (100mL; NSG100-P5-T3-SS1-SV-R, Anhui Kemi Instrument Co., Ltd.), the reactor cover was covered, sealed, and the air in the reactor cavity was exhausted by CO2 (repeatedly blown for 2-5min), and pressurized (1MPa CO2), and magnetic stirring (600rpm) was used throughout the process to ensure uniform mixing, and the temperature was monitored by a thermocouple above the reactor cover, and it was raised from 30°C to 150°C within 30min, and kept warm for 5min. The reactor was taken out, treated in an ice water bath for 5min, cooled to 30°C, the quartz liner was taken out, and a sand core funnel (G1-100mL) was used for vacuum filtration to obtain a solid residue. The solid residue was washed with deionized water three times (100 mL of deionized water each time) until the filtrate was neutral to obtain crude cellulose.

[0083] Table 1: Treatment effects of different holding times

[0084]

[0085] Table 2: Treatment effects at different temperatures

[0086]

[0087] Table 3: Treatment effects of different organic solvent-water volume ratios

[0088]

[0089] Table 4: Treatment effects of different amounts of agricultural and forestry processing waste and metal chlorides

[0090]

Claims

1. A method for efficiently deconstructing lignocellulose raw materials by coupling carbon dioxide with an organic solvent, characterized in that: include: The agricultural and forestry processing waste is washed, dried and crushed to obtain materials; the crushed materials are mixed with a reaction solvent, a metal chloride is added, the mixed materials are subjected to ultrasonic treatment to exhaust gas, and then placed in a reactor, the air in the reactor is replaced with CO2, and a heating treatment is performed under normal pressure or pressure, the materials are filtered, the solid residue is washed with water to neutrality, and vacuum freeze-dried to obtain crude cellulose, wherein the cellulose content of the crude cellulose is 68-75%, the hemicellulose content is 2-8%, and the lignin content is 4-5%; Wherein, the reaction solvent is a mixture of an organic solvent and water in a volume ratio of 80:20 to 100:0; the organic solvent is an organic solvent with a boiling point of 150 to 300°C; The metal chloride is one of FeCl3 or AlCl3; The normal pressure or pressurized pressure is: the pressure of CO2 is 0.1-2MPa; The heating treatment is as follows: the temperature is raised from room temperature to 150-190° C. at a heating rate of 4-5° C. / min while stirring, and the temperature is kept for 5-30 minutes, and then cooled to room temperature through an ice water bath.

2. The method for efficiently deconstructing lignocellulose raw materials by using carbon dioxide coupled with an organic solvent according to claim 1, characterized in that: The agricultural and forestry processing waste is one of rice straw, wheat straw, cotton straw, eucalyptus, birch, poplar and switchgrass; the agricultural and forestry processing waste is crushed to obtain materials with 20-40 mesh.

3. The method for efficiently deconstructing lignocellulose raw materials by using carbon dioxide coupled with an organic solvent according to claim 1, characterized in that: The drying process is as follows: drying the material with air blast at 105°C until the moisture content of the material is 0-10%.

4. The method for efficiently deconstructing lignocellulose raw materials by using carbon dioxide coupled with an organic solvent according to claim 1, characterized in that: The reaction solvent is a mixture of an organic solvent and water in a volume ratio of 80:20 to 90:

10.

5. The method for efficiently deconstructing lignocellulose raw materials by using carbon dioxide coupled with an organic solvent according to claim 1, characterized in that: The organic solvent is one of tetrahydrofurfuryl alcohol, 1,2-propylene glycol, glycerol, diethylene glycol and ethylene glycol.

6. The method for efficiently deconstructing lignocellulose raw materials by using carbon dioxide coupled with an organic solvent according to claim 5, characterized in that: The organic solvent is ethylene glycol.

7. The method for efficiently deconstructing lignocellulose raw materials by using carbon dioxide coupled with an organic solvent according to claim 1, characterized in that: The concentration of the metal chloride in the reaction solvent is 0.05-0.15 mol / L.

8. The method for efficiently deconstructing lignocellulose raw materials by using carbon dioxide coupled with an organic solvent according to claim 7, characterized in that: The concentration of the metal chloride in the reaction solvent is 0.08-0.1 mol / L.

9. The method for efficiently deconstructing lignocellulose raw materials by using carbon dioxide coupled with an organic solvent according to claim 1, characterized in that: The usage ratio of the agricultural and forestry processing waste to the metal chloride is 1:0.001 to 1:0.003 g / mol.

10. The method for efficiently deconstructing lignocellulose raw materials by using carbon dioxide coupled with an organic solvent according to claim 9, characterized in that: The usage ratio of the agricultural and forestry processing waste to the metal chloride is 1:0.0016-1:0.002 g / mol.

11. The method for efficiently deconstructing lignocellulose raw materials by using carbon dioxide coupled with an organic solvent according to claim 1, characterized in that: The heating treatment is as follows: the temperature is raised from room temperature to 150-170° C. at a heating rate of 4-5° C. / min while stirring, and the temperature is kept for 5-30 minutes, and then cooled to room temperature through an ice water bath.

Citation Information

Patent Citations

  • Method for preparing bio-oil by performing two-step grading hydrothermal liquification on lignocellulose under CO2 atmosphere

    CN107858170A

  • Method for extracting cellulose from agricultural straw wastes

    CN109722932A